Development of Fonts for African Scripts: Using Computer Technologies to Preserve Africa s Written Heritage - Rovenchak, Andrij (AAeO - Afrikanistik-Aegyptologie-Online, 2010)
The issue of the font making for modern indigenous African scripts is briefly discussed. Encoding problems, including the Unicode standard, are addressed. Font samples are presented for some of the scripts.